“The Best Laid Plans of Marx and Men”: Mitch Podolak, Revolution, and the Winnipeg Folk Festival - MacDonald, Michael (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
Mitch Podolak said, “Pete Seeger and Leon Trotsky lead to everything in my life, especially the Winnipeg Folk Festival.” This article discusses the creation of the Winnipeg Folk Festival (WFF) in 1974 as Podolak’s first attempt to fuse his ten years of Trotskyist political training with his love for folk music. His intention was to create a Canadian folk festival which would embody the politically resistant nature of the Trotskyist international movement for the purpose of challenging the Canadian liberal capitalist democratic system on a cultural front. Heavily influenced by the American Communist Party’s use of folk music, Podolak believed that the folk song and its performance were socially important. This importance, he believed, stemmed from the social cohesion that could be created within a festival performance space. This space, when thoughtfully organized, could have the ability to create meaning. The relationships between the artistic director, the folk singer, the folk song and the festival audience become intertwined to dialectically create the meaning of the song and the space simultaneously defining folk music